Cerebral ischemia during hemodialysis—finding the signal in the noise. Issue 3 (11th February 2018) - MacEwen, Clare; Watkinson, Peter; Tarassenko, Lionel; Pugh, Christopher
Abstract: Hemodialysis patients have multiple risk factors for small vessel cerebrovascular disease and cognitive dysfunction. Hemodialysis itself may cause clinically significant neurological injury through repetitive cerebral ischemia. However, supporting evidence to date consists of epidemiological associations, expert opinion, and small, single‐centre studies of variable methodological quality. Isolating the impact of intra‐dialytic hemodynamic instability from underlying renal and vascular disease on clinically relevant functional outcomes would require very large, controlled studies, given the heterogeneity and confounding comorbidities of the population, and the complex relationship between blood pressure and cerebral oxygen delivery. There has been an increase in complementary physiological studies looking directly at intra‐dialytic cerebral oxygen balance, which have provided supporting evidence for the occurrence of cerebral ischemia, often independently of hemodynamics. Data suggesting a relationship between these measures of oxygen balance and functional outcomes is only hypothesis‐generating at this stage. We advocate the testing of interventions that aim to reduce intra‐dialytic cerebral hypoxia (rather than hypotension) in sufficiently powered studies, followed by correlation with validated, longitudinal assessment of clinically relevant neurological damage.